PENGARUH ISKEMIA TERHADAP PENINGKATAN KOLAGEN PADA KORPUS KAVERNOSUM - Alif, Sabilal (Indonesian Journal of Urology, 2008)
Objective: To demonstrate that ischemia causes elevation of collagen in cavernous body. Material & Method: Sample used in this study were male adult rabbits (Oryctalagus Cuniculus) 6 – 9 months of age. Partial ligation of both common iliac arteries was performed in this study to induce cavernous body ischemia. Results: Collagen mean for 7 x 24 hours ligation group (group B) increased to 113,83/200 compared to the collagen mean for the 2 x 24 hours ligation group (group A) which was 91,08/200 and collagen mean for control group (group C) which was 86,90/200. There was collagen elevation on treatment group which caused by ligation (Anova, F value= 12,110 and p=0,0001). Conclusion: Ischemia may elevate collagen in cavernous body.